Preface - Raniecki, B.; Tanaka, K. (Archives of Mechanics, 1999)
The present issue of Archives of Mechanics contains the submitted and reviewed contributions to the Polish-Japanese Workshop on "B Testing and Modelling the Behaviour of Shape Memory Alloys", which was organised as an accompanying event at the 32nd Solid Mechanics Conference: SolMec ’98, held in Zakopane, September 1 - 5, 1998.